THE MEASUREMENT OF POTENTIAL RISK OF FIRE AND EXPLOSION AT GAS STASION IN TO ANTICIPATE NON-MILITARY THREATS - Rizky Aferdiansyah; Novita Affuwani; Mas Ayu Elita Hafizah; Robertus Heru Triharjanto; Widianto Nugroho (Universitas Mercu Buana, 2021)
Gas stations (SPBU in Indonesia) have the potency for fire and explosion hazards due to the storage and distribution of flammable liquids, one of which is Pertamax. This can be a non-military threat in the dimension of public safety because if it occurs, the resulting loss could be very large in terms of material or life. This study aims to determine the risk of fire and explosion at Indonesian gas station. This study uses Dow's Fire and Explosion Index in asimulated case method. The potential for fire and explosion or the value of the Fire Explosion Index (F&EI) in the simulated case is 111,24. The actual exposure radius is 29.62 m and the damage factor to the Pertamax storage tank is 63%. The results of the study have a risk level that is classified as Intermediate, so it is necessary to control risks such as increasing active protection and is expected to be an input in efforts to safeguard against non-military threats so as to reduce the impact of risks and losses that occur in the Pertamax storage tank.